The New Professionalism Character in Education: Framing the Management Issue - Prasetyo, Muhammad Anggung Manumanoso; Fadhli, Muhammad (Tadbir : Jurnal Studi Manajemen Pendidikan, 2023)
Professional character development necessitates a variety of outcome-based evaluation strategies. This article suggests modifying the concept and substance of the lecturer evaluation system to improve professional lecturer characteristics. Qualitative research using the grounded approach, technological data mining, and experience Data analysis on MPI professional practice at IAIN Lhokseumawe utilizing analytic research. The study's research boundaries represent instructors' professional competency in the aims of the Tri Dharma of higher education. The results of the study revealed that the new subject offered by the MPI IAIN Lhokseumawe. To begin, lessons learned about professional traits based on religious beliefs and job evaluations have implications for classroom instruction, research, and community outreach. Second, the identification of empirical indicators of professionalism outcome attainment is identified by performance assessment reports and procedures for building a culture of professionalism that is regarded as ideal for formalization through a reward and punishment system. Third, professional growth in higher education is accomplished by strategic evaluative personal skills, substantial education, institutional training, job autonomy, and adherence to an ethical code. When the principle of professionalism is studied, the practical implication will be the establishment of a global management professional who will contribute qualitatively to the demands of the industrial world and raise the growth of the global economy as a whole.